Analysis of a Novel Resistive Film Absorber for Suppression of Electromagnetic Radiation in System-in-Packages - Shuyun Huo; Yan Li; Xiaoyong Lei; Zhe Sun; Heyuan Yu; Bingheng Li; Lidan Fang; Shaojie Xu; Ning Jin; Erping Li (International Journal of Antennas and Propagation)
This paper presents a new method to suppress the electromagnetic radiation between the heatsink and packaging substrate in the system-in-package by using a resistance film absorber. The proposed absorber is designed with the indium tin oxide sputtered on both sides of the glass substrate, and the top layer adopts the combination of Jerusalem cross-shaped, ring-shaped, and L-shaped resistive film to expand the bandwidth. The unit size of the absorber is 0.14λL×0.14λL and the thickness is 0.049 λL. It has an absorptivity of more than 90% in the frequency range of 21 GHz to 55 GHz with polarization insensitivity, and angular stability. Moreover, the radiated electric field from the chip package at 3 m is significantly reduced when employing the proposed absorber, and the maximum suppression of the electric field reaches 18 dB. Finally, the measurement results are carried out to verify the simulation results. Both simulation and experiment results demonstrate that the proposed absorber has excellent radiation suppression, which can be properly applied to electromagnetic interference suppression of the printed circuit board.